Description of The Knowledge and Attitude of The Husband Towards Contraception Method of Men's Surgery (MOP) on Poris Plawad Utara Subdistrict, Cipondoh, Tangerang City, Banten - Mahmudin, Mahmudin (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
In 2050 the world population is expected to reach 9 billion people, with the world population growth rate of about 1.3% which means there are about 78 million additional inhabitants 1 year (UNPFA, 2002). In Indonesia, the population growth rate between 2000 – 2002 is about 1.3% or about 7.3 million people every year. Indonesia is the fourth largest population country in the world after the People's Republic of China, India, and the United States (Ahmad, 2009). The data provides a warning that the world's population, especially the Indonesian population, is still relatively high, without any efforts to control the population so that the results of development in various sectors will be difficult to achieve to the maximum. Based on a preliminary survey of researchers interviewing Couples of Childbearing Age (PUS) it turns out that 6 out of 10 Couples of Childbearing Age do not know or understand about MOP contraceptives or vasectomies. Therefore, the researchers are interested in researching about the description of the husband's knowledge about contraceptives on Jl. KH. Mustofa RT 03/04 Kel. Poris Plawad Utara, Cipondoh, Tangerang City, Banten.